The navigation of sexual identity between novice therapists and their queer clients: therapists’ perspectives - Kgosamang, Rebaone (University of the Witwatersrand, Johannesburg, 2021)
Queer research related to psychotherapy is relatively scarce. The necessary emphasis of queer research on the HIV epidemic, social inclusion and exclusion and political and legislative issues surrounding the queer community has resulted in a relative neglect of mental health issues. Given the historical context of homophobia in psychology and psychiatry, therapists’ experiences of working with queer clients are important to investigate. The current study aimed to explore how novice therapists navigate sexual identity with their queer clients in therapy. A qualitative study was conducted in which six (6) participants were interviewed using a semi-structured interview schedule. The study’s sample comprised of an intern Clinical Psychologist, a newly qualified Educational Psychologist and four newly qualified Clinical Psychologists who are all in private practice. Demographically, there were two white men both of whom are cisgendered and identify as queer and four black women of whom are all cisgendered with one identifying as queer and the rest as heterosexual. A thematic analysis was conducted on the results that emerged from the interviews with the participants. The following three major themes emerged: Disclosing sexual identity, Taking care to avoid pathologising queer clients and therapy shaped by therapists’ own sexual identity. The results indicated the complexity involved in navigating sexual identity in psychotherapy. Therapists experienced a process of initial unexpected openness, followed by an awareness of guardedness as well as a growing awareness of their clients’ expectations of prejudice in their encounter with sexual identity in therapy. This appeared to be influenced by clients’ internalised homophobia. Additionally, therapists’ own sexual identity influenced how they broached sexual identity in the room, with heterosexual therapists noting a fear around misunderstand and queer therapists acknowledging a struggle with overidentification. The results implicitly revealed a gap within training programmes. Implications for practising therapists are discussed.
A research project submitted in partial fulfilment of the requirements for the degree of MA by coursework and research report in the field of Clinical Psychology in the Faculty of Humanities, University of the Witwatersrand, Johannesburg. 2021
Keywords: Sexual identity; Psychotherapy; Internalised homophobia; Homosexuality; Heterosexuality; SDG-3: Good health and well-being